Tourism as a Factor of Increased Competitiveness of the Region - Burtseva, Tatiana A.; Khvoevskaya, Larisa I.; Prokhorova, Victoria V.; Chernikova, Victoria E.; Basyuk, Anait S. (International Journal of Economics and Financial Issues, 2016)
The paper considers tourism and tourism operations as one of the key priorities of increased competitive strengths of Russian regions, their area, socio- economic status and image. One of the presented ways of sustainable and effective development of tourism industry of the region is the formation of large-scale interregional, international associations conducting their activities for increased main competitive indicators and living conditions. Thus, the main function of performers of tourism operations of the considered territory will be to control work of regional agencies of local government that promotes increased quality of tourist management and defines the key possible priorities of development of the issues to solve being as follows: -development of a procedure of sharing experiences between regions; -attraction of an investor and additional financial means in the course of development of travel industry; - creation and promotion of positive image of the district, region and tourist base; - development of interregional projects which are in physical proximity of territories that promotes increase number of tourist routes and increases the potential of regions. Keywords: region, competitiveness, tourism, interregional ties, innovations, state JEL Classifications: F43, L83, O49